Impact of claudin‐10 deficiency on amelogenesis: Lesson from a HELIX tooth. Issue 1 (28th July 2022) - Obtel, Nicolas; Le Cabec, Adeline; Nguyen, Thè Nghia; Giabicani, Eloise; Van Malderen, Stijn J. M.; Garrevoet, Jan; Percot, Aline; Paris, Céline; Dean, Christopher; Hadj‐Rabia, Smail; Houillier, Pascal; Breiderhoff, Tilman; et al.
Abstract: In epithelia, claudin proteins are important components of the tight junctions as they determine the permeability and specificity to ions of the paracellular pathway. Mutations in CLDN10 cause the rare autosomal recessive HELIX syndrome (Hypohidrosis, Electrolyte imbalance, Lacrimal gland dysfunction, Ichthyosis, and Xerostomia), in which patients display severe enamel wear. Here, we assess whether this enamel wear is caused by an innate fragility directly related to claudin‐10 deficiency in addition to xerostomia. A third molar collected from a female HELIX patient was analyzed by a combination of microanatomical and physicochemical approaches (i.e., electron microscopy, elemental mapping, Raman microspectroscopy, and synchrotron‐based X‐ray fluorescence). The enamel morphology, formation time, organization, and microstructure appeared to be within the natural variability. However, we identified accentuated strontium variations within the HELIX enamel, with alternating enrichments and depletions following the direction of the periodical striae of Retzius. These markings were also present in dentin. These data suggest that the enamel wear associated with HELIX may not be related to a disruption of enamel microstructure but rather to xerostomia. However, the occurrence of events of strontium variations within dental tissues might indicate repeated episodes of worsening of the renal dysfunction that may require further investigations. Abstract : Our study investigates a third molar collected from a HELIX (Hypohidrosis, Electrolyte imbalance, Lacrimal gland dysfunction, Ichthyosis and Xerostomia) female patient, by microanatomical and physicochemical approaches. The enamel morphology, formation time, organization, microstructure and overall elemental composition appear to be within the natural variability. However, accentuated strontium variations are found within the enamel and dentin, with alternating enrichments and depletions following the direction of the periodical striae of Retzius. This suggests that the CLDN10 mutation, responsible for the HELIX syndrome, does not alter enamel formation. The strontium marked events may reflect the renal dysfunction and the resulting ionic imbalance.